2011
DOI: 10.1530/eje-11-0499
|View full text |Cite
|
Sign up to set email alerts
|

RET/PTC rearrangement in benign and malignant thyroid diseases: a clinical standpoint

Abstract: Cytological examination of fine needle aspiration biopsy is the primary means for distinguishing benign from malignant nodules. However, as inconclusive cytology is very frequent, the introduction of molecular markers in the preoperative diagnosis of thyroid nodules has been proposed in recent years. In this article, we review the clinical implications of preoperative detection of rearrangements of the RET gene (RET/papillary thyroid carcinoma (PTC)) in thyroid nodules. The prevalence of RET/PTC in PTC depends… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(61 citation statements)
references
References 69 publications
0
59
0
2
Order By: Relevance
“…RET/PTC, BRAF, NTRK, RAS and PAX8-PPAR␥ mutations have been frequently explored for diagnosis of thyroid cancer. Gene expression profiling and microRNA studies have identified a variety of potential molecular markers to help distinguish benign from malignant thyroid neoplasms especially for nodules that are classified as indeterminate for malignancy by FNAB [36,37,45,34,[90][91][92][93][109][110][111][112][113]178,[180][181][182]. The inability to exclude malignancy in these nodules may often lead to unnecessary surgery or two step surgical procedures.…”
Section: Molecular Targets In Histopathological Diagnosis and Classifmentioning
confidence: 99%
“…RET/PTC, BRAF, NTRK, RAS and PAX8-PPAR␥ mutations have been frequently explored for diagnosis of thyroid cancer. Gene expression profiling and microRNA studies have identified a variety of potential molecular markers to help distinguish benign from malignant thyroid neoplasms especially for nodules that are classified as indeterminate for malignancy by FNAB [36,37,45,34,[90][91][92][93][109][110][111][112][113]178,[180][181][182]. The inability to exclude malignancy in these nodules may often lead to unnecessary surgery or two step surgical procedures.…”
Section: Molecular Targets In Histopathological Diagnosis and Classifmentioning
confidence: 99%
“…et al , Marotta et al 2011a) and biological significance of the mutation had been hampered by the application of different detection methods. The low percentage of tumours having RET rearrangements as driver mutational event represents a crucial limitation for clinical application of the mutation, both in the diagnostic and the prognostic setting.…”
Section: :11mentioning
confidence: 99%
“…The use of highly sensitive techniques also allowed the detection of non-clonal mutational events, namely the presence of RET rearrangements in a small proportion of tumour cells or even in a single cell. This paradoxically hampered the possible clinical application of the mutation as molecular marker, in both diagnostic and prognostic settings (Marotta et al 2011a). Indeed, several authors reported the presence of RET/PTC in benign thyroid diseases, including not only Hashimoto's thyroiditis (Wirtschafter et al 1997, Sheils et al 2000, Rhoden et al 2006) but also thyroid nodules revealing benign histology (Cinti et al 2000, Elisei et al 2001.…”
Section: :11mentioning
confidence: 99%
“…Receptor tyrosine kinase are rearranged during transfection (RET) for activation and about 15 RET gene rearrangement was identified in papillary thyroid carcinoma (PTC) among which RET/PTC1 and RET/PTC3 are the most common type (Marotta et al 2011). RET was detected in mammalian (human) oocytes (Farhi et al 2010) and are expressed in embryos throughout the early development with an increase after the early blastocyst stage (Kawamura et al 2008).…”
Section: Ret Tyrosine Kinase (Ret)mentioning
confidence: 99%